2020
DOI: 10.1590/0034-7167-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Measuring suicide risk in the elderly with non-institutionalized depression: an integrative review

Abstract: Objective: Analyze the state of the art about instruments, at national and international levels, for assessing the risk of suicide in elderly people with depression assisted in the community. Methods: Integrative review of 38 complete articles, published in journals indexed in the databases: US National Library of Medicine (PubMed Central), Scopus, CINAHL and Web of Science, located using controlled descriptors combined with Boolean operators: elderly OR aged OR older OR elder OR geriatric AND depression AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In several studies, depression is consistently confirmed as the most important factor in suicidal ideation in the elderly, and the more severe the depressive symptoms, the higher the suicidal ideation. 14,15 Representative examples of these factors include age, gender, economic status, social support, smoking, sleep, chronic diseases, life satisfaction, and psychosocial well-being. 16 However, predicting whether a particular person will develop suicidal ideation even if the risk factors above are identified is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, depression is consistently confirmed as the most important factor in suicidal ideation in the elderly, and the more severe the depressive symptoms, the higher the suicidal ideation. 14,15 Representative examples of these factors include age, gender, economic status, social support, smoking, sleep, chronic diseases, life satisfaction, and psychosocial well-being. 16 However, predicting whether a particular person will develop suicidal ideation even if the risk factors above are identified is difficult.…”
Section: Introductionmentioning
confidence: 99%